Systematic Approach to Malalignment Type Ventricular Septal Defects - Yoo, Shi‐Joon (J Am Heart Assoc, 2020)
Various congenital heart diseases are associated with malalignment of a part of the ventricular septum. Most commonly, the outlet septum is malaligned toward the right or left ventricle. Less commonly, the whole or a major part of the ventricular septum is malaligned in relation to the atrial septal plane. Although the pathological conditions associated with ventricular septal malalignment have been well recognized, the descriptions are often confusing and sometimes incorrect. In this pictorial essay, we introduce our systematic approach to the assessment of malalignment type ventricular septal defects with typical case examples. The systematic approach comprises description of the essential features of malalignment, including the following: (1) the malaligned part of the ventricular septum, (2) the reference structure, (3) the mechanism of malalignment, (4) the direction of malalignment, and (5) the severity of malalignment.